A aprendizagem da docência de uma professora iniciante : um olhar com foco na intermulticulturalidade - Palomino, Thaís Juliana (2009)
The diversity invades the school through the culture and beliefs of students and their families, minority groups etc. The attention to issues such as diversity, difference, equality and inequality it is urgent. In this scenario, the teaching can not only field of teaching contents. It needs to be intermulticultural, understood as that one that considers the diversity and differences and conceives the inaqualities as constructed in the discursives and social relations. Moreover, the teacher, whose practices are based on intermulticulturality, conducts its activities with political sensitivity to transform social reality. Under these assumptions, this research was carried out with a beginner teacher in their first two years of practice in teaching (with two classes of first grade) in order to assist it in the construction of teaching practices based on intermulticulturalidade. Initially we offer a course for continued formation on the thematic that had as main objective to help the participants realize ideological traps and disarm them in which we, teachers, fall in the classroom. Soon after, one of the teachers of the course expressed interest in continuing to work and was monitored for two semesters. In its first two years of teaching in two different schools, one countrified and one urban, the teacher went through all the difficulties to the beginning of the career: a professional loneliness, fluctuations between discovery and survival, the desire to abandon a career were reported feelings for her. While we folloied her in the classroom, we see the ideological traps in which the teacher fell and especially the reasons that led to fall, that is, to understand its cultural conceptions, as interrogated it them and to help it in this process. In interviews and informal conversations the teacher explained some stereotypical beliefs and values, while they, in their work in the classroom, invested in some practices that they considered and worked with the diversity and difference between their students and which the students in a positive way. Some approaches and practices based on removals intermulticulturality are perceived, also, as fruit of adversity the start of teaching.